Nasal Carriage of Vancomycin- and Methicillin-Resistant Staphylococcus aureus among Intermediate Students of Urban and Rural Schools of Muthanna Province in Iraq - Hantoosh, Saad Muslim (Iraqi Journal of Pharmaceutical Sciences, 2022)
Staphylococcus aureus is one of the common causative agents of infections, from asymptomatic carriers to healthy individuals. It can colonize anterior nares of carriers with a high capability to resist different antibiotics. Students are susceptible to bacterial infection due to some factors, including poor health habits and surrounding school conditions. This study screened the rate of vancomycin- and methicillin- resistant Staphylococcus aureus nose carriers among secondary students in rural and urban schools and its association with some sociodemographic factors. The study sample included 300 male/female students aged 15-20 years from 12 schools of rural and urban areas during the period from November 2020 till May 2021. It was found that males are 2.3 times more of MRSA nose carriage and the rate of infections was higher in rural schools than urban whether among males or females. The prevalence of MRSA was 72/300 (24%) among students with 15/72 (21%) MDR-MRSA isolates with high resistance to Clindamycin and Erythromycin at rate 46% and 42% respectively, and a resistance ranging between (20-26) % for Gentamycin, Levofloxacin, Trimethoprim/Sulfamethoxazole, Rifampin, and Nitrofurantoin with high sensitivity to Vancomycin at 4% of resistance. There was no significant association between MRSA incidence with both medication and chronic diseases despite the 19% of students were self-medicating. Most schools were suffering from a shortage of potable water, disinfectants, and first aid materials. Students lack health awareness about transmissible diseases with unhealthy habits spread among students, as specialized health teams did not visit most schools.